Dichlorvos and dimethoate residues in betelvine (Piper betle) foliage - DIXIT, B S; JOHRI, J K; BANERJI, R (The Indian Journal of Agricultural Sciences, 2013)
Separate field trials were conducted to study the magnitude of dicblorvos and dimethoate residues in betel leaves(Piper betel C). Betel leaves were sprayed thrice at fortnightly intervals with the insecticides at a concentration of 0.0Sand 0.10%. The amount of initial residues of dichlorvos aod dimethoate was 12.54-12.59 and 11.69-11.89 ppmrespectively at 0.05% dose, aod 24.82-24.88 and 21.06-21.88 ppm at 0:10%, For both the insecticides residues fellwell below the tolerance limit during the first 14 days, after which the betel leaves cao be harvested.